2011
DOI: 10.1111/j.1600-0404.2010.01398.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and European comparison of dementia in a ≥75-year-old composite population in Spain

Abstract: Dementia prevalence in Spain is comparable to other European populations, while a high number of undiagnosed cases live in the community. The potential impact of Mediterranean diet, hypertension control and decreasing vascular risk factors is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 22 publications
3
23
0
2
Order By: Relevance
“…As regards the major dementia subtypes, the results confirmed what is being found by other studies: that AD is the most frequent subtype in older adults, followed by VD [35,36,37]. AD was diagnosed in 63.7% of the cases, a result similar to those obtained by other studies that have shown AD to affect more than 50% of cases of individuals aged 65 or more years [6,28], and more than 60% among still older age groups [38,39].…”
Section: Discussionsupporting
confidence: 81%
“…As regards the major dementia subtypes, the results confirmed what is being found by other studies: that AD is the most frequent subtype in older adults, followed by VD [35,36,37]. AD was diagnosed in 63.7% of the cases, a result similar to those obtained by other studies that have shown AD to affect more than 50% of cases of individuals aged 65 or more years [6,28], and more than 60% among still older age groups [38,39].…”
Section: Discussionsupporting
confidence: 81%
“…Data showed that incidence [10,12,13,18,32,34,39,42,43,49], prevalence [16,27,30,36,46], and mortality rates [25] of AD increased with age (Tables 3-5). In all studies assessing incidence [13,18,26,39,43], prevalence [16,27,30,38,43,46], or mortality rates [21,24] by gender, AD, and mortality due to AD were more common in females (regardless of their age) compared to males. For the incidence of AD, the ratio of females:males was approximately the same in all of the studies, with the incidence of AD in women being approximately twice that observed in males of a comparable age.…”
Section: Epidemiological Data On Admentioning
confidence: 93%
“…France [36,45], zero for Germany, four for Italy [16,27,28,38], one for the Netherlands [43], four for Spain [17,29,30,46], one for the UK [15], and six for the USA [11,13,14,31,32,40]. Table 4 presents results on the prevalence of AD.…”
Section: Epidemiological Data On Admentioning
confidence: 97%
“…In a multi-center study with eight European countries, including Spain and Sweden, the incidence and prevalence of different dementia diagnoses, particularly of vascular dementia, differed greatly between countries [11, 12]. However, another study did not find differences in the odds of dementia between a composite of Spanish studies and the Kungsholmen study, in Sweden [14]. Prevalence variations are apparent even within countries, for example, in Spain, age- and sex-adjusted prevalence for dementias for +70 populations ranged between 3% and 12% depending on the geographical area [13, 15].…”
Section: Introductionmentioning
confidence: 99%